2004
DOI: 10.1073/pnas.0403639101
|View full text |Cite
|
Sign up to set email alerts
|

DNA targeting of rhinal cortex D2 receptor protein reversibly blocks learning of cues that predict reward

Abstract: When schedules of several operant trials must be successfully completed to obtain a reward, monkeys quickly learn to adjust their behavioral performance by using visual cues that signal how many trials have been completed and how many remain in the current schedule. Bilateral rhinal (perirhinal and entorhinal) cortex ablations irreversibly prevent this learning. Here, we apply a recombinant DNA technique to investigate the role of dopamine D2 receptor in rhinal cortex for this type of learning. Rhinal cortex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 47 publications
(66 reference statements)
2
58
0
Order By: Relevance
“…The abundance and nature of observed gene expression differences, generally reflecting changes in discrete cell populations, suggest that phenotypic differences may be driven combinatorially by many small differences in the spatial regulation of gene expression. Functional implications for variations of expression patterns within structures noted in this study are suggested in reports that indicate a role for dopamine D2 receptor acting in entorhinal cortex during associative visual learning in nonhuman primates (17), as well as for variations in creativity correlated with receptor binding in the human thalamus (18). Furthermore, a recent study of striatopallidal neurons and dopaminergic regulation of GABAergic synaptic transmission highlights the functional relevance of the complex interplay of receptor expression, cell type, and circuitry within highly localized brain regions (19).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The abundance and nature of observed gene expression differences, generally reflecting changes in discrete cell populations, suggest that phenotypic differences may be driven combinatorially by many small differences in the spatial regulation of gene expression. Functional implications for variations of expression patterns within structures noted in this study are suggested in reports that indicate a role for dopamine D2 receptor acting in entorhinal cortex during associative visual learning in nonhuman primates (17), as well as for variations in creativity correlated with receptor binding in the human thalamus (18). Furthermore, a recent study of striatopallidal neurons and dopaminergic regulation of GABAergic synaptic transmission highlights the functional relevance of the complex interplay of receptor expression, cell type, and circuitry within highly localized brain regions (19).…”
Section: Discussionmentioning
confidence: 93%
“…Therapeutics affecting the dopamine and serotonin systems are among the most commonly prescribed neuroactive drugs, covering a variety of indications ranging from depression and schizophrenia to movement disorders. The dopamine D2 receptor alone is a site of action for a number of therapeutics and has roles in locomotion, emotion, cognition, and drug abuse (17,20,21). Differences in individual responses to such drugs have been observed in humans (22) and previous studies have shown that C57 and DBA mice respond differently to drugs known to affect dopamine signaling (23).…”
Section: Discussionmentioning
confidence: 99%
“…Fiducial markings as in Figure 4. cortex in which the D 2 receptor is crucial for learning the relation of the cue to the schedule states (Liu et al, , 2004. There is, however, a difficulty.…”
Section: Possible Origins Of the Signalsmentioning
confidence: 99%
“…Richmond and his colleagues Shidara and Richmond, 2002;Shidara et al, 1998;Sugase-Miyamoto and Richmond, 2005;Bowman et al, 1996;Liu et al, 2004;Ravel and Richmond, 2006;La Camera and Richmond, 2008) have investigated many behavioral and neural aspects of an appealingly simple problem for monkeys that they call the reward schedule task. The task is illustrated in figure 1A.…”
Section: Introductionmentioning
confidence: 99%